KEMAMPUAN PEMECAHAN MASALAH MAHASISWA CALON PENDIDIK MATEMATIKA - NOLA NARI (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2014)
This research was inspired from the result of a research under the title: “Analisis kemampuan pemecahan masalah matematis mahassiswa program studi tadris matematika.” This research was done to know and describe how was the students’ ability to solve mathematic probelm as math teacher candidate in Geometri Transformasi subject registered in 2012/2013 academic year of Mathematic department of Tarbiyah Faculty of STAIN Batusangkar. The design of this research was the combination of quantitative and qualitative by using descriptive approach. The instrument of this research was test and interview. The data was analyzed through data triangulation, data reduction, data presentation, and making conclusion. The result of the research showed that the students’ ability from high group was very satisfactory. The students’ ability from avarage group was satisfactory. And, the students’ ability from low group was almost satisfactory.Kata kunci: Kemampuan pemecahan masalah, matematis